DIAGNOSIS AND MANAGEMENT OF POSTPARTUM DEPRESSION - Alison Chang Yen Pin; Nyoman Ratep; Wayan Westa (Faculty of Medicine, Udayana University, 2013)
Postpartum depression is an affective disorder that affects predominantly in women after childbirth. The typical characteristics are feeling miserable, fatigue, weariness, and there are changes in sleeping and eating patterns. History taking from patient and family is the essential part to diagnose the patient, which Edinburgh Postnatal Depression Scale (EPDS) is a screening tool frequently used. Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria is utilized to establish if the patient is experiencing postnatal depression. Postnatal depression can become a major illness if not treated seriously. There are many treatments available to treat the postpartum depression such as drugs, psychotherapy, and/or alternative therapy. With suitable treatment, it can increase the relationship between mother-child and the quality life of the family. Keywords: Postpartum depression, affective disorder, psychotherapy